2014
DOI: 10.1155/2014/985141
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Complications of Paracentesis: A Systematic Review of the Literature

Abstract: Introduction. Large volume paracentesis is considered a safe procedure carrying minimal risk of complications and rarely causing morbidity or mortality. The most common complications of the procedure are ascitic fluid leakage, hemorrhage, infection, and perforation. The purpose of this study was to evaluate all hemorrhagic complications and their outcomes and to identify any common variables. Methods. A literature search for all reported hemorrhagic complications following paracentesis was conducted. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 30 publications
1
62
0
5
Order By: Relevance
“…The practitioner should avoid the upper quadrants, given the proximity of the liver and spleen to the abdominal wall. They should also avoid 11 and 2 o'clock angles of the abdomen to prevent inadvertently puncturing the inferior epigastric arteries, a known cause of hemorrhagic complications [66]. A pocket of 3-4 cm between the abdominal wall and the free-floating loops of bowel is adequate and is usually found in the lateral-most aspect of the abdomen [11].…”
Section: Paracentesis and Thoracentesismentioning
confidence: 99%
“…The practitioner should avoid the upper quadrants, given the proximity of the liver and spleen to the abdominal wall. They should also avoid 11 and 2 o'clock angles of the abdomen to prevent inadvertently puncturing the inferior epigastric arteries, a known cause of hemorrhagic complications [66]. A pocket of 3-4 cm between the abdominal wall and the free-floating loops of bowel is adequate and is usually found in the lateral-most aspect of the abdomen [11].…”
Section: Paracentesis and Thoracentesismentioning
confidence: 99%
“…These recommendations can be found in Section 8.6 of the respective labels. 3,4 1306 Correspondence [ 1 5 5 # 6 C H E S T J U N E 2 0 1 9 ]…”
Section: Responsementioning
confidence: 99%
“…Abdominal wall bleeding is a rare but lethal complication of LVP. [49][50][51] It has often been anecdotally attributed to underlying coagulopathy and thrombocytopenia in patients with cirrhosis. However, literature is divided over this and there are reports both supporting and refuting this hypothesis.…”
Section: Extrahepatic Osseous/soft-tissue Metastases Of Hepatocellulamentioning
confidence: 99%
“…However, literature is divided over this and there are reports both supporting and refuting this hypothesis. [48][49][50][51] Although the exact incidence of haemorrhagic complication in patients with cirrhosis and portal hypertension is unknown, studies have reported incidence rates of between 0.8 and 3.0%. 51 Signs and symptoms of haemorrhage can manifest from minutes to days after the procedure.…”
Section: Extrahepatic Osseous/soft-tissue Metastases Of Hepatocellulamentioning
confidence: 99%